1993
DOI: 10.3233/ves-1993-3304
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Orientation and Posture During and Following Weightlessness: Human Experiments on Spacelab Life Sciences 1

Abstract: The 4 payload crew members of the Spacelab Life Sciences 9-day space flight in 1991 were subjected to limited vestibular testing in flight as well as pre and post flight. Major differences in individual “perceptual style” appeared in their reaction to the visual-vestibular stimuli in the rotating dome experiment, and especially in the extent to which nondirectional tactile cues served to anchor the subjective vertical and body postural reactions. The ability of subjects to point to remembered target positions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Future work could test the respective contributions of shoulder, elbow, wrist, and finger muscles to LF estimation, with the use of ballasts, elastic chords, and counterweights attached to various points of the arm during isometric force production. Such experiments can allow the effects of muscle activity to be distinguished from other effects specific to the conditions of microgravity and hypergravity, conditions that also affect vestibular inputs, postural control 35,36 , spatial orientation [54][55][56] , limb position sense [57][58][59] , and stress 60 . Our protocol did not allow us to probe the participants' conscious perception of forces.…”
Section: Discussionmentioning
confidence: 99%
“…Future work could test the respective contributions of shoulder, elbow, wrist, and finger muscles to LF estimation, with the use of ballasts, elastic chords, and counterweights attached to various points of the arm during isometric force production. Such experiments can allow the effects of muscle activity to be distinguished from other effects specific to the conditions of microgravity and hypergravity, conditions that also affect vestibular inputs, postural control 35,36 , spatial orientation [54][55][56] , limb position sense [57][58][59] , and stress 60 . Our protocol did not allow us to probe the participants' conscious perception of forces.…”
Section: Discussionmentioning
confidence: 99%
“…One could also test the impact of hand posture (e.g., flipping the hand 180°) on LF reproduction to control for biomechanical asymmetries. These experiments can be performed on the ground and allow the effects of muscle activity to be distinguished from other effects specific to the conditions of microgravity and hypergravity, conditions that also affect vestibular inputs, postural control, 37 , 38 spatial orientation, 65 , 66 , 67 limb position sense, 68 , 69 , 70 and stress. 71 Besides, our protocol did not allow us to probe the participants’ conscious perception of forces.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that human proprioception diminishes in hypogravity; limb matching tasks are less effectively completed ( Lackner and DiZio, 1992 ) as well as approximations of limb position ( Bringoux et al, 2012 ; Young et al, 1993 ). Mouchnino et al (1996) found that anticipatory postural adjustments were notably absent below standard Earth gravity.…”
Section: Introductionmentioning
confidence: 99%
“…To examine this, previous investigations have focused on manipulating the gait characteristics of an individual within an Earth-like environment. Few studies have sought to examine hysteresis in human gait through manipulation of the environment itself ( Bringoux et al, 2012 ; Ivanenko et al, 2002 ; Young et al, 1993 ). Yet even a brief consideration of the ontology of gait reveals the absolute importance of environmental conditions to human locomotion.…”
Section: Introductionmentioning
confidence: 99%